2011
DOI: 10.1158/0008-5472.can-10-3606
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 Contributes to the Progression of Human T-cell Acute Lymphoblastic Leukemias

Abstract: The importance of microenvironmental factors for driving progression in leukemia has been debated.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
112
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 44 publications
4
112
0
3
Order By: Relevance
“…Most prior studies have focused on signaling via IL-7 (Dibirdik et al, 1991;Barata et al, 2004aBarata et al, ,b,c, 2005González-Garcia et al, 2009;Shochat et al, 2011;Silva et al, 2011) or mutational activation of intermediates in the PI3K-Akt pathway Gutierrez et al, 2009). The importance of PI3K-Akt activation in T-ALL is underscored by multiple studies showing that PI3K-Akt/mTOR inhibitors block growth/survival of T-ALL cells (Avellino et al, 2005;Wei et al, 2006;Palomero et al, 2007;Chiarini et al, 2009;Cullion et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most prior studies have focused on signaling via IL-7 (Dibirdik et al, 1991;Barata et al, 2004aBarata et al, ,b,c, 2005González-Garcia et al, 2009;Shochat et al, 2011;Silva et al, 2011) or mutational activation of intermediates in the PI3K-Akt pathway Gutierrez et al, 2009). The importance of PI3K-Akt activation in T-ALL is underscored by multiple studies showing that PI3K-Akt/mTOR inhibitors block growth/survival of T-ALL cells (Avellino et al, 2005;Wei et al, 2006;Palomero et al, 2007;Chiarini et al, 2009;Cullion et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Although previous works have focused on the role of IL-7 signaling in T-ALL, including effects on downstream PI3K-Akt activation (Dibirdik et al, 1991;Barata et al, 2004aBarata et al, ,b,c, 2005González-Garcia et al, 2009;Shochat et al, 2011;Silva et al, 2011), we considered that insulin-like growth factor (IGF)-1 receptor (IGF1R) may also play an important role. IGFs and their receptors regulate normal cell growth and contribute to transformation and growth of malignant cells in many contexts (Pollak et al, 2004).…”
Section: Pharmacologic Inhibition Of Igf1r Compromises T-all Cell Growthmentioning
confidence: 99%
“…Thymocyte:TEC crosstalk is essential at multiple stages of T-cell development. TECs express NOTCH ligands and IL-7, which are required for differentiation of normal T-cells (13)(14)(15), but have also been implicated in T-ALL tumorigenesis (10,16). Thus, nascent lymphoma cells may coopt signals in the thymic microenvironment to promote tumor growth.…”
mentioning
confidence: 99%
“…Thus, nascent lymphoma cells may coopt signals in the thymic microenvironment to promote tumor growth. Previous studies demonstrated that stromal support is required for ex vivo survival of mouse and human T-ALL cells (10,(17)(18)(19)(20) and implicated IL-7 and NOTCH1 signaling in promoting tumor survival (10,(16)(17)(18). Together, these findings suggest that TECs might promote T-ALL.…”
mentioning
confidence: 99%
“…IL-7 binds to a receptor (IL-7R) that is composed of cluster of differentiation (CD) 127 (IL-7Rα) and CD132 (γc), which is found on lymphoid progenitor cells, BCP cells and T cells. It has been demonstrated that IL-7 facilitates the proliferation and survival of leukemia cells (8)(9)(10), contributes to the progression and relapse of leukemia (11,12) and induces resistance to chemotoxins (13), thus contributing to the pathogenesis of ALL. As a result, identifying the leukemia-specific mediators of these IL-7-driven effects may enable the therapeutic targeting of this pathway.…”
Section: Introductionmentioning
confidence: 99%